PENGARUH STRUKTUR KEPEMILIKAN KELUARGA TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTY, REAL ESTATE DAN KONSTRUKSI BANGUNAN - Evita Vianita Sari; Juniarti Juniarti Juniarti (Business Accounting Review, 2018)
Family firms still dominate in Indonesia, where family firms have disadvantages and advantages that effect firm performance. Previous research on the influence of family firms was also inconsistent. This study aimed to know the effect of family ownership structure on firm performance. Firm performance was measured by using ROA. The control variables used were good corporate governance, intensity of competition, capital structure. The sample used in this research was the companies of property, real estate and building construction sector that met certain criteria and was analyzed by using multiple linear regression. The result of this research showed that family ownership structure had significant effect to firm performance. Capital structure had negative significant effect to firm performance. The intensity of competition and good corporate governance variable had no significant effect to firm performance.